Hukum Adat di Era Modernisasi - Harniwati Harniwati (Universitas Sumatera Barat, 2024)
The customary law is recognized as a form of law in the life and culture of Indonesian society, regulated in the 1945 Constitution. Customary law is the values ​​that develop in society regarding truth and justice. In terms of legal substance, the 1945 Constitution expressly provides a place and basis for the application of legal norms and legal institutions originating from laws that live and apply in society (living live) where customary law is made part of national law. The confirmation of the Constitution is related to the inclusion of two new articles in the second amendment to the 1945 Constitution, namely article 18 B Paragraph (2) which explains that the state recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with development of society and the principles of the Unitary State of the Republic of Indonesia as regulated in law. Second, Article 28 I Paragraph (3) which contains an explanation regarding the recognition of customary law which states that the cultural identity and rights of traditional communities are respected in line with developments over time and civilization. From the formulation of these two articles, it can be concluded that every Indonesian citizen who lives under state regulations, both citizens and government officials, without exception, is required to uphold the laws that apply in the life and culture of Indonesian society, including criminal law, civil or customary law.